2009
DOI: 10.1186/ar2878
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the first cardiovascular event in patients with systemic lupus erythematosus - a prospective cohort study

Abstract: IntroductionCardiovascular disease (CVD) is a major cause of premature mortality among Systemic lupus erythematosus (SLE) patients. Many studies have measured and evaluated risk factors for premature subclinical atherosclerosis, but few studies are prospective and few have evaluated risk factors for hard endpoints, i.e. clinically important cardiovascular events (CVE). We investigated the impact of traditional and lupus associated risk factors for the first ever CVE in a longitudinal cohort of SLE patients.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
117
3
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 49 publications
15
117
3
6
Order By: Relevance
“…Although physical activity can prevent long-term consequences of SLE such as obesity, osteoporosis and premature cardiovascular and cerebrovascular diseases risk (Petri et al 1992;Svenungsson et al 2001;Bruce et al 2003;Oeser et al 2005;Goldberg et al 2009;Gustafsson et al 2009;Urowitz et al 2008;Volkmann et al 2010), in John Hopkins Lupus Cohort, 70% of patients reported a sedentary lifestyle (Petri et al 1992). Although physical activity reduces the patients' fear of disability, there is still a great difference of opinion about the time of onset, type and intensity of that activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although physical activity can prevent long-term consequences of SLE such as obesity, osteoporosis and premature cardiovascular and cerebrovascular diseases risk (Petri et al 1992;Svenungsson et al 2001;Bruce et al 2003;Oeser et al 2005;Goldberg et al 2009;Gustafsson et al 2009;Urowitz et al 2008;Volkmann et al 2010), in John Hopkins Lupus Cohort, 70% of patients reported a sedentary lifestyle (Petri et al 1992). Although physical activity reduces the patients' fear of disability, there is still a great difference of opinion about the time of onset, type and intensity of that activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although physical activity reduces the patients' fear of disability, there is still a great difference of opinion about the time of onset, type and intensity of that activity. Knowing the physiology of physical activity will be reasonable to apply it during treatment or as an early prevention of the disease's sequelae (Krupp et al 1991;Gustafsson et al 2009;Volkmann et al 2010). It is unknown which type and intensity of physical activity contributes most to the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Los mecanismos subyacentes a una acelerada aterosclerosis en el LES son complejos y son áreas de activa investigación. Aunque los riesgos tradicionales como la dislipidemia y el tabaquismo han sido demostrados como factores predictores de riesgo cardiovascular en pacientes con LES, el lupus en sí mismo es un factor de riesgo independiente para enfermedad cardiovascular [7,14,23]. Varios tipos de enfermedad cardiovascular fueron observados entre los pacientes con LES, incluyendo pericarditis, miocarditis, enfermedad del sistema de conducción, vasculitis, enfermedad valvular, así como también enfermedad coronaria, enfermedad cerebrovascular, insuficiencia cardiaca congestiva y enfermedad arterial periférica [11].…”
Section: Discussionunclassified
“…En el estudio LUMINA [24] la presencia de anticuerpos antifosfolipídicos estuvo significativamente asociada a un incremento del riesgo 4 veces mayor de tener un evento cardiovascular en un promedio de tiempo de aproximadamente 6 años. La presencia de anticuerpos antifosfolipídicos también estuvo asociada a un incremento de 4 veces más el riesgo de presentar un infarto de miocardio, accidente cerebrovascular en un estudio de 182 mujeres con diagnóstico de LES seguidas en promedio por 8,3 años [23,27]. Si bien en nuestro estudio se analizó la presencia del diagnóstico de SAF y se encontró una asociación significativa con los accidentes cerebrovasculares, no se realizó un estudio centrado en la positividad o en los títulos de los anticuerpos antifosfolipídicos de forma específica, pero la asociación encontrada sugiere esta relación coincidiendo con la literatura.…”
Section: Discussionunclassified
“…Attempts to find risk factors for premature death, that is identification of the aspects of lifestyle which contribute to death, are closely connected with Dahlgren and Whitehead's modern model of health [2]. There are numerous population studies presenting the problem [3][4][5][6][7][8][9][10]. Long-term studies on changes in mortality in the second half of the 20th century confirm that the state of health in all age groups, also in the productive age, has deteriorated with regard to non-communicable diseases, especially cardiovascular diseases, in Poland until 1991.…”
Section: Introductionmentioning
confidence: 99%